Q fever prevention in Australia: general practitioner and stakeholder perspectives on preparedness and the potential of a One Health approach - Md R. Rahaman; Katherine Hodgetts; Adriana Milazzo; Helen Marshall; Anne‐Lise Chaber; Deane Crabb; Peng Bi (Elsevier, 2022)
Abstract Objective: To examine stakeholder perspectives on the factors of an effective approach to reduce Q fever risk including disease prevention, and the perceived potential benefits of a One Health framework. Methods: Semi‐structured interviews were conducted with general practitioners (GPs), veterinarians, government authorities, researchers, and representatives from the farming industry. Transcripts were thematically analysed. Results: Six major themes were identified as key factors underpinning an effective approach to Q fever: understanding Q fever burden; effective surveillance; the role of general practitioners and other stakeholders; barriers and enablers of vaccination; an integrated approach; and increased Q fever awareness. Most participants perceived GPs to play a central role in disease detection, notification, treatment and prevention through health promotion and vaccination, despite GPs acknowledging limited awareness of Q fever. Participants suggested leadership is required from the Department of Health (DoH) to foster inter‐sectoral communication and collaboration. Conclusions: A One Health approach holds opportunities for zoonosis prevention. We recommend that medical curricula and professional development be enhanced, zoonosis working group networks strengthened, government‐industry partnerships established, and relevant stakeholders included within an integrated program. Implications for public health: Updating medical curricula, GP professional development programs and inter‐sectoral collaboration led by health departments may reduce Q fever burden.